Cross-cultural variations in the prevalence and presentation of anxiety disorders. (February 2011) - Marques, Luana; Robinaugh, Donald J; LeBlanc, Nicole J; Hinton, Devon
Considerable cross-cultural variation exists in the prevalence and presentation of the anxiety disorders as defined by the fourth edition of the Diagnostic and Statistical Manual. Researchers debate whether this variation represents cultural differences in the phenomenology of universal disorders or the existence of unique culturally constructed disorders. This article reviews recent literature on the prevalence and presentation of five anxiety disorders: generalized anxiety disorder, social anxiety disorder, panic disorder, specific phobia and post-traumatic stress disorder, both across countries and within the USA. This article indicates that certain anxiety disorders (e.g., generalized anxiety disorder and panic disorder) may vary greatly in rate across cultural groups. It indicates that the clinical presentation of anxiety disorders, with respect to symptom presentation and the interpretation of symptoms, varies across cultures. A difference in catastrophic cognitions about anxiety symptoms across cultures is hypothesized to be a key aspect of cross-cultural variation in the anxiety disorders. Future research directions are suggested.